Mutation profile of BBS genes in patients with Bardet-Biedl syndrome: an Italian study - Elena Manara; Stefano Paolacci; Fabiana D'Esposito; Andi Abeshi; Lucia Ziccardi; Benedetto Falsini; Leonardo Colombo; Giancarlo Iarossi; Alba Pilotta; Loredana Boccone; Giulia Guerri; Marica Monica; et al. (BMC, 2019)
Abstract Background Bardet-Biedl syndrome (BBS) is a rare inherited multisystemic disorder with autosomal recessive or complex digenic triallelic inheritance. There is currently no treatment for BBS, but some morbidities can be managed. Accurate molecular diagnosis is often crucial for the definition of appropriate patient management and for the development of a potential personalized therapy. Methods We developed a next-generation-sequencing (NGS) protocol for the screening of the 18 most frequently mutated genes to define the genotype and clarify the mutation spectrum of a cohort of 20 BBS Italian patients. Results We defined the causative variants in 60% of patients; four of those are novel. 33% of patients also harboured variants in additional gene/s, suggesting possible oligogenic inheritance. To explore the function of different genes, we looked for correlations between genotype and phenotype in our cohort. Hypogonadism was more frequently detected in patients with variants in BBSome proteins, while renal abnormalities in patients with variations in BBSome chaperonin genes. Conclusions NGS is a powerful tool that can help understanding BBS patients' phenotype through the identification of mutations that could explain differences in phenotype severity and could provide insights for the development of targeted therapy. Furthermore, our results support the existence of additional BBS loci yet to be identified.